2020
DOI: 10.1016/j.eats.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The Outside-In, Percutaneous Release of the Medial Collateral Ligament for Knee Arthroscopy

Abstract: The outside-in, percutaneous release of the medial collateral ligament (MCL) is a technique used to increase the medial tibiofemoral joint space during arthroscopy to facilitate the use of instrumentation and improve visualization without causing iatrogenic cartilage damage. A recent systematic review of the literature has shown this technique to be efficacious and safe, with no evidence of associated short-or long-term complications. This technique has been used for this indication by the senior author withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
(35 reference statements)
0
33
0
Order By: Relevance
“…This is similar to the findings of Moran et al, Javidan et al, and Hinton. [8][9][10] We found out that releasing the medial meniscus does not lead to valgus instability following arthroscopic treatment for CIBHMT. This finding was similar to those of Moran et al, who found out that controlled release of the MCL in tight knees allowed easier handling in posterior medial meniscus tears and a better understanding of tear configurations, avoiding iatrogenic chondral damage and the MCL injury healed uneventfully.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…This is similar to the findings of Moran et al, Javidan et al, and Hinton. [8][9][10] We found out that releasing the medial meniscus does not lead to valgus instability following arthroscopic treatment for CIBHMT. This finding was similar to those of Moran et al, who found out that controlled release of the MCL in tight knees allowed easier handling in posterior medial meniscus tears and a better understanding of tear configurations, avoiding iatrogenic chondral damage and the MCL injury healed uneventfully.…”
Section: Discussionmentioning
confidence: 85%
“…5 This is not unconnected with the limited exposure of the medial compartment, leading to incomplete and inadequate repair that subsequently results in high failure rates in the early stages and osteochondral damage. 8 We do a subcutaneous release of the posterior fibers of the MCL to improve the exposure of the medial compartment for better visualization, anatomic reduction of the torn meniscus, and its surface attachment to the wall. This maneuver ensures a complete stable repair with good surface contact instead of the suture points contacts in poorly visualized joints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Many previous studies have established that MCL release is a safe and minimally harmful technique. [16][17][18][19] MCL pie crusting has typically generated grade I MCL laxity without saphenous nerve or vein By means of medial collateral ligament release, the ramp lesion, which is usually covered by the medial femoral condyle, can be seen from the standard anterolateral viewing portal. By use of the FasT-Fix system from anteromedial portal, the ramp lesion is repaired.…”
Section: Discussionmentioning
confidence: 99%